Leptin and Soluble Leptin Receptor Levels in Plasma and Risk of Type 2 Diabetes in U.S. Women: A Prospective Study - Sun, Qi (American Diabetes Association, 2010)
OBJECTIVE: We prospectively examined plasma levels of leptin and soluble leptin receptor (sOB-R), as well as their interactions with other diabetes risk factors, in relation to type 2 diabetes to elucidate the complex relation between these two biomarkers and diabetes risk. RESEARCH DESIGN AND METHODS: Of 32,826 Nurses' Health Study participants who provided blood samples during 1989–1990, 1,054 incident case subjects of type 2 diabetes were identified and confirmed during 1990–2004 and 1,254 matched control subjects were selected. Plasma leptin and sOB-R levels were measured among these participants. RESULTS: After multivariate adjustment for BMI, lifestyle practices, and dietary factors, sOB-R levels were significantly associated with a lower risk of type 2 diabetes. In comparison with women in the lowest quintile, the ORs (95% CI) of developing type 2 diabetes were 0.73 (0.55–0.96), 0.51 (0.38–0.68), 0.42 (0.31–0.57), and 0.39 (0.28–0.54; P for trend < 0.0001) for women in the second to fifth quintiles of sOB-R levels, respectively. In contrast, plasma leptin levels were not significantly associated with the risk of type 2 diabetes: The OR (95% CI) was 0.82 (0.62–1.10; P for trend = 0.46) comparing the highest with the lowest quintile of leptin levels. sOB-R levels were consistently associated with a decreased risk of type 2 diabetes at various levels of leptin or high-molecular-weight adiponectin. CONCLUSIONS: These data suggest a strong inverse association between plasma sOB-R levels and risk of type 2 diabetes, independent of BMI, leptin, and adiponectin levels.